Strategi Kepala Madrasah Dalam Meningkatkan Kinerja Guru PAI di Mts Muhammadiyah Banjarmangu Banjarnegara - Nira Tri Nanda; Robingun Suyud El Syam; Nur Farida (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The performance of Islamic religious education teachers has a significant impact on the spiritual and academic development of students in madrasas. This article reviews the strategies of madrasa heads in improving the performance of Islamic religious education teachers. Research highlights the importance of transformational leadership and fostering professionalism as key elements in such strategies. Through an open and collaborative communication approach, madrasah heads can motivate teachers to develop their pedagogical and scientific competencies. In addition, providing ongoing support, training and relevant curriculum development is an integral part of the strategy. The practical and theoretical implications of this research are also discussed to support improving the quality of Islamic religious education in madrasas. This thesis aims to find out the strategy of madrasah heads in improving the performance of Islamic Religious Education teachers at Mts Muhammadiyah Banjarmangu Banjarnegara. This thesis uses a qualitative field approach. The research location is Mts Muhammadiyah Banjarmangu Banjarnegara. The data sources used include primary data, namely the results of interviews with madrasa heads, Islamic Religious Education teachers, madrasa committees, and madrasa supervisors. Secondary data was obtained from documentation, photos of activities and madrasa profiles. The data collection techniques used are observation, interviews and documentation. Data processing and analysis techniques are carried out through three stages, namely: data reduction, data presentation, and drawing conclusions.